Automatic Milking in Greece: First Insight into Udder Health of Dairy Cows - Themistokleous, KS; Sakellariou, N; Kougioumtzis, A; Kiossis, E (Journal of the Hellenic Veterinary Medical Society, 2022)
Udder health is a key factor for dairy cows’ productivity and welfare. This study presents the first insight into dairy cows’ udder health after the introduction of automatic milking systems in Greece. Four farms with Holstein dairy cows and automatic milking systems enrolled in the study. Data from their milking records were utilized, from January 2020 to December 2021. Variables employed in the assessment were cow daily milk yield (DMY), number of daily milkings / cow, individual cow somatic cell count (SCC), proportion of cows with elevated somatic cell count (ELSCC) / month, proportion of cows with chronically ELSCC (ChrELSCC) / month and number of new ELSCC (NewELSCC) cases per 100 cows / month. Two years’ mean milking frequency was 2.72 milkings / cow / day, ranged from 2.47 to 2.98, and decreased from 2020 to 2021. Mean cow SCC was 193,000 cells/mL, ranged from 70,000 to 260,000 cells/mL, and increased from 2020 to 2021. Mean cow DMY was 37.2 kg, ranged from 29.6 to 43.6 kg. Heifers had lower mean SCC than cows and mean SCC increased from early to late lactation stages. On a monthly basis, 37.06 % and 40.06 % of the cows were ELSCC in 2020 and 2021, respectively, and most of them were chronic. The highest ELSCC was observed in late lactation stage. Fresh cows presented the highest number of NewELSCC / 100 cows / month, both years of the study. Overall udder health in the four automatic milking farms of this study was better than conventional farms in Greece. Precision dairy farming should utilize daily milking data for data-driven management, monitoring of chronically ELSCC, and early detection, treatment and prevention of new infections.